Photo-CIDNP NMR methods for studying protein folding. - Mok, K; Hore, P (2004)
Chemically induced dynamic nuclear polarization (CIDNP) is a nuclear magnetic resonance phenomenon that can be used to probe the solvent-accessibility of tryptophan, tyrosine, and histidine residues in proteins by means of laser-induced photochemical reactions, resulting in significant enhancement of NMR signals. CIDNP offers good sensitivity as a surface probe of protein structure and is particularly powerful in time-resolved NMR measurements. Real-time, rapid-injection protein refolding experiments permit the observation of changes in the accessibility of specific residues during the folding process. CIDNP pulse-labeling gives information on the accessibility of residues in partially structured proteins (e.g., molten globule states) whose NMR spectra are broad and poorly resolved. Heteronuclear two-dimensional (15)N-(1)H CIDNP techniques allow identification of surface-accessible residues with improved resolution and sensitivity. These methods offer residue-specific structural and kinetic information on transient folding intermediates and other partially folded states of proteins that are not readily available from more routine NMR techniques.